2021
DOI: 10.1371/journal.pone.0259891
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B and C among female sex workers in Togo, West Africa

Abstract: Background Hepatitis B and C are endemic in sub-Saharan Africa, with prevalence among the highest in the World. However, several challenges impede the progression towards the elimination of viral hepatitis by 2030 as suggested by the World Health Organization Global health sector strategy on viral hepatitis, including the lack of knowledge on the scale of this epidemic in the region. The aim of this study was to estimate the prevalence of hepatitis B and C among female sex workers (FSW) in Togo. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Gathering relevant data in some high endemicity countries, including countries in the WHO African, South-East Asian and Western Pacific regions is made more difficult due to criminalisation and/or stigmatisation of inclusion health populations for example CSW, PWID and LGBTQ+ communities. Depending on the sampling methods, available data suggest intermediate to high HBV prevalence in CSWs, PWID, and incarcerated people in African populations ( Bitty-Anderson et al, 2021 ; Degenhardt et al, 2017 ; Dolan et al, 2016 ; Scheibe et al, 2020 ). Fear of discrimination by healthcare workers, possible legal consequences and refusal of services are just some of the barriers deterring inclusion health populations from seeking care and remaining in longer term follow up ( Duby et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gathering relevant data in some high endemicity countries, including countries in the WHO African, South-East Asian and Western Pacific regions is made more difficult due to criminalisation and/or stigmatisation of inclusion health populations for example CSW, PWID and LGBTQ+ communities. Depending on the sampling methods, available data suggest intermediate to high HBV prevalence in CSWs, PWID, and incarcerated people in African populations ( Bitty-Anderson et al, 2021 ; Degenhardt et al, 2017 ; Dolan et al, 2016 ; Scheibe et al, 2020 ). Fear of discrimination by healthcare workers, possible legal consequences and refusal of services are just some of the barriers deterring inclusion health populations from seeking care and remaining in longer term follow up ( Duby et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…frequency of unprotected sex [11,12]. Several studies have shown that low adherence to condom use, multiple sexual partners, unsafe sexual practices, illicit drug use, and co-infection with other STI increase the risk of HBV and HCV transmission [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that low adherence to condom use, multiple sexual partners, unsafe sexual practices, illicit drug use, and co-infection with other STI increase the risk of HBV and HCV transmission. FSW also have a higher risk of contracting STI from their non-paying partners than from their paying clients (10,11).…”
Section: Introductionmentioning
confidence: 99%